Remote, small-scale, 'greener' routes of ammonia production. (20th October 2018) - Arora, Pratham; Sharma, Ishan; Hoadley, Andrew; Mahajani, Sanjay; Ganesh, Anuradda
Abstract: The techno-economic feasibility of low-carbon–based ammonia (NH3 ) production has been explored in this study. Black coal and a eucalyptus-based biomass, available in the vicinity of a carbon dioxide (CO2 ) sequestration site, have been chosen as the two carbon-based feedstocks. The scale of the production of NH3 has been chosen to match the production of a bulk industrial Ammonium Nitrate/Fuel Oil (ANFO) explosives manufacturing facility. The production of NH3 from any carbon-based feedstock implicitly involves a CO2 -removal step; therefore, only CO2 pressurisation to the supercritical state is required before transporting it to the storage location. In order to gain a better understanding of the economic and environmental trade-offs, two representative flowsheets have been modelled in Aspen Plus ® simulation software for the two feedstocks. A Natural Gas (NG)-based NH3 process has also been modelled for comparison. Material and energy balance data from the Aspen Plus ® simulation has been used to predict the economics and carbon footprint of NH3 production from different feedstocks. A cradle-to-gate Life Cycle Assessment (LCA) has been performed to predict the environmental hotspots. A genetic algorithm based Multi-objective Optimisation (MOO) has generated Pareto plots that represent the minimum cost of NH3 production against different CO2 footprints. For a similar CO2 footprint, the coal-based NH3 process has been found to be more economic than the biomass-based process. However, the biomass-based process has the potential to be carbon negative by capturing the biogenic CO2, which is not possible in a coal-based process. The cost of carbon capture in coal-based NH3 production has been estimated to be between 11 and 19 U S $ / t C O 2 e q, which is significantly lower than the cost of CO2 capture from coal-based power generation (usually reported to be in the range of 40–60 U S $ / t C O 2 ). Highlights: Analysis of small-scale NH3 production from different carbon-based feedstocks. Comparison of the carbon footprint from green feedstock and/or post treatment of CO2 emissions. Comparison of different flowsheets based on economic parameters and CO2 emissions. Multi-Objective Optimisation to visualize economic and environmental trade-offs. Consistent set of economic assumptions and LCA methodology for reliable comparison.